Effectiveness of a neuromuscular and proprioceptive training program in preventing anterior cruciate ligament injuries in female athletes - Mandelbaum, B. R.; Silvers, H. J.; Watanabe, D. S.; Knarr, J. F.; Thomas, S. D.; Griffin, L. Y.; Kirkendall, D. T.; Garrett, W. (The American Journal of Sports Medicine, 2005)
Background: Among female athletes it has not been established whether a neuromuscular and proprioceptive sports-specific training program will consistently reduce the incidence of anterior cruciate ligament injuries.